2011
DOI: 10.1002/mrm.23136
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic imaging with prospective motion correction and retrospective phase correction

Abstract: Motion-induced artefacts in magnetic resonance spectroscopic imaging are much harder to recognize than in imaging experiments and can therefore lead to erroneous interpretation. A method for prospective motion correction based on an optical tracking system has recently been proposed and has already been successfully applied to single voxel spectroscopy. In this work, the utility of prospective motion correction in combination with retrospective phase correction is evaluated for spectroscopic imaging in the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Several groups have found significantly improved MRS data quality, if motion correction was applied (Andrews-Shigaki et al, 2011; Boer et al, 2012; de Nijs et al, 2009; Ernst and Li, 2011; Helms and Piringer, 2001; Hess et al, 2012; Hess et al, 2011; Keating and Ernst, 2012; Kim et al, 2004; Lange et al, 2012; Lin et al, 2009; Posse et al, 1993; Thiel et al, 2002; Zaitsev et al, 2010). A common approach is the retrospective correction of frequency and phase, in particular for SVS (Ernst and Li, 2011; Helms and Piringer, 2001; Lin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several groups have found significantly improved MRS data quality, if motion correction was applied (Andrews-Shigaki et al, 2011; Boer et al, 2012; de Nijs et al, 2009; Ernst and Li, 2011; Helms and Piringer, 2001; Hess et al, 2012; Hess et al, 2011; Keating and Ernst, 2012; Kim et al, 2004; Lange et al, 2012; Lin et al, 2009; Posse et al, 1993; Thiel et al, 2002; Zaitsev et al, 2010). A common approach is the retrospective correction of frequency and phase, in particular for SVS (Ernst and Li, 2011; Helms and Piringer, 2001; Lin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported significantly improved spectral quality for both single-voxel spectroscopy (SVS) and 2D-MRSI, when retrospective, prospective, or a combination of both motion corrections is used (Andrews-Shigaki et al, 2011; Boer et al, 2012; de Nijs et al, 2009; Ernst and Li, 2011; Hess et al, 2012; Hess et al, 2011; Keating and Ernst, 2012; Lange et al, 2012; Lin et al, 2009; Thiel et al, 2002; Zaitsev et al, 2010). While retrospective correction alone (e.g., frequency/phase alignment of separately saved averages) can improve data quality to a certain degree (Helms and Piringer, 2001; Kim et al, 2004; Posse et al, 1993), prospective real-time motion correction (i.e., updating the MR sequence in real-time) can further improve data quality (Andrews-Shigaki et al, 2011; Hess et al, 2012; Hess et al, 2011; Lange et al, 2012; Zaitsev et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The topic of prospective motion correction has gained popularity in the last few years resulting in numerous new applications including fMRI (101, 102), DWI (103, 104), and spectroscopy (105-107). Although it is an extremely promising approach for neuroimaging, it does have some limitations, including practical considerations (e.g., marker fixation for external tracking systems) and uncorrectable effects (e.g., motion-related B0 distortions (108)).…”
Section: Artefact Mitigation Strategiesmentioning
confidence: 99%